Pengaruh Atmosfer Terhadap Kepuasan dan Niatan Perilaku Konsumen di Toko,Kota Malang - Hersanti, Nova Juwita; Ratnawati, Kusuma (Universitas Brawijaya, Indonesia, 2012)
The purpose of this research is to enrich the empirical evidence about the influence of atmospherics on satisfaction and behavioral intentions of customers at Toko Oen, Malang. Research sample is consumerat Toko Oen which amounts to 100, consistions of 50 local consumers and 50 foreign consumers. Sampling method applies purposive sampling technique. Partial Least Square (PLS) analysis is then performedto reveal the relationship between atmospherics satisfaction and behavioral intentions. The results reveals that atmospherics has a positive and significant influence on satisfaction and behavioral intentions of overall consumers, bath local and foreign consumers. Satisfaction has positive and significant influence on behavioral intentions of overall consumers, whereas satisfaction does not have any significant influenceof satisfaction on behavioral intentions of local consumers.Keywords: atmospherics, satisfaction, behavioral intentions, Toko